Metodologi Penafsiran Abdullah Yusuf Ali (Tafsir Linguistik The Holy Of Qur’an) - Ulfah Nur Azizah; Fuhair Annahdhi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2021)
This paper reveals the methodology of interpretation of Abdullah Yusuf Ali in his work The Holy Qur'an: Text Translation and Commentary. To obtain a broader understanding of interpretation, the author uses a synchronic linguistic approach in its presentation. His work The Holy Qur'an is quite famous in the Muslim world because of the different interpretations he uses. Usually the commentators use Arabic in interpreting the Qur'an, but Abdullah Yusuf Ali uses English so that it is easier for Westerners to study the Qur'an. In addition, he writes touch and interpretation in a poetic style aimed at expressing a wider meaning and beauty. He tries to translate and interpret the verse with a socio-spiritual experience in which in his vision there are various perspectives, including the mistakes of human perspective to the spiritual world.